PENGARUH PENGGUNAAN PUPUK UREA TERHADAP SERANGAN HAMA KEPIK COKLAT (Riptortus linearis Fabricius) PADA KEDELAI (Glycine max L.) - Mulyaningsih, Liliek (JURNAL AGRI-TEK, 2017)
The purpose of this study was to determine the effect of the use of urea fertilizer on the level of pest attacks Riptortus linearis. This research was conducted in experimental garden of Faculty of Agriculture of Soerjo Ngawi University located on Jalan Raya Cepu Ngawi East Java from October to December 2016. The materials used in this research are Grobogan Groundnut seed variety and IAC.100 strain, R. linearis pest, Gauze, compost, 8 kg polybag and Urea fertilizer. The tools used in this research are hoes, hoods, gembor, sample boards, bamboo, jars, stationery and cameras. This research was conducted using Division of Distributed Plot (RPT), the main plot consisted of two varieties (V) and sub plots consisted of four doses (N), so there were eight experimental treatment combinations.The results showed that there was no interaction between Urea fertilization with Grobogan and IAC.100 strains. The use of Urea fertilizer at a dose of 100 kg per hectare causes the number of pods to be attacked higher and there is a significant difference when compared to the dose of 75 kg per hectare, 50 kg per hectare and without treatment. The IAC.100 strain shows a higher degree of susceptibility than Grobogan varieties, especially on the number of pods, seeds attacked, healthy seeds and attacked seeds. keywords: urea fertilizer, brown ladybird (riptortus linearis fabricius), Soybean (glycine max l.)